Quantum resonances in reflection of relativistic electrons and positrons; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 355 : Channeling 2014: Charged & Neutral Particles Channeling Phenomena - Eykhorn Yu. L. Yury Leonidovich; Korotchenko K. B. Konstantin Borisovich; Pivovarov Yu. L. Yuriy Leonidovich; Takabayashi Yu. Yush (2015, 2015)
Title screen